(untitled) (Revista de Ciências Agroveterinárias, 2017)
During the 2012/2013 agricultural year, in the city of Campo Novo do Parecis, MT, the study aimed to analyze the spatial variability of soybean and of the fertility attributes of Typic Tropudox under no-tillage. The sampling grid for data collect was installed in an area of 5.0 ha. The productivity of soybeans, plant population, organic matter, P, Ca+2, Mg+2, K+, Al+3, H+ + Al+3, pH (CaCl2), sum bases, cation exchange capacity and base saturation were evaluated. A classic descriptive analysis was carried out with the help of the SAS statistical software, correlation and regression analysis with Excel and semivariograms were then modeled for all attributes, giving the respective cross-validations and kriging charts with the GS+ 7.0 software. Most surveyed attributes presented spatial dependence, and modeled their semivariograms by predominantly Gaussian type. The geostatistical ranges used for the attributes analyzed should not be less than 43.8 m, being the distance at which the attribute values are related to each other. The study of the variability of soil attributes and the adoption of techniques that help in the management of soil, such as geostatistics, is essential to proper plant development.